Impact of Subsyndromal Delirium Occurrence and Its Trajectory during ICU Stay - Serafim, Rodrigo B. (2022)
Funding Information: This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors. Publisher Copyright: © 2022 by the authors.